KEBIJAKAN REMILITARISASI SHINZO ABE DITINJAU DARI TWO LEVEL GAMES THEORY - Sebayang, Tino Rila; Sopyan, Muhammad Syakir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2022)
This study discusses about Japan's defense policy during of Prime Minister Shinzo Abe administration which carried out a strategy of strengthening the role of the military (remilitarization) in maintaining state sovereignty and creating stability in the dynamics of security in the East Asia region. But on the other hand, this remilitarization policy actually clashed with Japan's pacifist country status as stated in the Japanese Constitution 1947 especially Article 9. This pacifist constitution explicitly means about limitations on the role of the Japan Self Defense Force (JSDF) in resolving international disputes. Instead, Japan handed over its international security affairs under the security cooperation with the United States (American Umbrella). The aims of this study is to examine how the dynamics of determining Japan's remilitarization policy as a response for regional security complexities in terms of the situation at the domestic and international levels. By using analytical descriptive methods and qualitative approaches, this research was compiled based on sources obtained from books, journals, articles, state documents and mass media. The theory used in this study is the two level games theory purposed by Robert Putnam. The results of this study indicate that in order to achieve a win-set in determining remilitarization policies at the domestic level, public legitimacy and support from the Japanese government are the determining factors. Meanwhile, the expansion of the JSDF's role through strengthening security cooperation with the United States and alliance countries in the region is a determining factor for win-sets at the international level. By elaborating the win-set at both levels, the remilitarization policy is the right strategy for Japan to respond uncertainties dynamics of regional security.